PEMBELAJARAN PENDIDIKAN AKHLAK SISWA SDN 01 PONDOK KELAPA KABUPATEN BENGKULU TENGAH - Tarjuli Tarjuli (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2018)
The study aims to describe the Learning of Moral Education Student Elementary School 01 Pondok Kelapa Central Bengkulu  District. The objectives  are detailed  as follows: (1) Describe  the planning  of learning,  (2) Implementation of Learn- ing Morals Education. (3) Evaluation of Learning  Morals Education. This research  is qualitative  descriptive  research  with case study approach. The object  of this studyis Learning  Moral Education in review of planning,  implementation, and  evaluation at SDN 01 Pondok Kelapa, Central Bengkulu Regency.  This research  data  comes from observation with field note notes (field notes),  interviews, and documentation. Based on data  analysis, it is known that in general,  the learning of morality of students in SDN 01 Pondok Kelapa,  Central  Bengkulu  Regency  covers  3 main  activities, namely:  (1) Education Planning  of Morals, (2) Implementation of Learning  of Morals Education, and  (3) Evaluation of Moral Learning.  Learning  planning  includes  the preparation of learning  tools in the form of: a) 1. Formulating learning  objectives,  2. Development of teaching  materials,  3. Learning  methods, 4. Learning  media,  5. Resources  / Materials teaching,  6. Evaluation. Learning  implementation consists of: initial activities, core activities (learning activities) and final activities, c) evaluation consists of: 1. Written, oral, assignment, and observation test